The emerging role of neutrophil extracellular traps in endometritis - Li, Hongyan; Liu, Ling; Wang, Junrong; Zhao, Weiliang (Frontiers in Immunology, 2023)
Endometritis is a kind of common obstetric disease in women, usually caused by various pathogenic bacteria. Neutrophil infiltration is one of the most important pathological features of endometritis. Neutrophils can reach the uterine cavity through the endometrium, and make early response to the infection caused by the pathogen. Neutrophil extracellular traps (NETs), a meshwork of chromatin fibers extruded by neutrophils, have a role in entrapping microbial pathogens. It has been confirmed that NETs have a strong antibacterial effect and play crucial roles in the occurrence and development of various diseases. However, while killing pathogenic bacteria, excessive NETs formation may cause immune damage to the body. NETs are present in endometrium of female domestic animals in different physiological periods, especially post-mating, postpartum and in the presence of lesions, especially in endometritis, playing a key role of immune clearance, protection and regulation. Meanwhile, NETs and its products might contribute to a reduction in physical clearance and persistent endometritis. In brief, NETs is a double-edged sword and it may play a different role in the development of endometritis, which may be beneficial or harmful, and its specific mechanism needs further study. Here we provide an overview of the role of NETs in the development of endometritis and the regulatory role of selenium on NETs formation and endometritis.